One-Pot Microwave-Assisted Synthesis of Carbon Dots and in vivo and in vitro Antimicrobial Photodynamic Applications - Romero, María Paulina; Alves, Fernanda; Stringasci, Mirian Denise; Buzzá, Hilde Harb; Ciol, Heloísa; Inada, Natalia Mayumi; Bagnato, Vanderlei Salvador (Frontiers in Microbiology, 2021)
Carbon-based photosensitizers are more attractive than the other ones based on their low cost, high stability, broadband of light absorption, tunable emission spectra, high quantum yield, water solubility, high resistance to metabolic degradation and selective delivery. These properties allow multiple applications in the field of biology and medicine. The present study evaluated in vitro and in vivo the antimicrobial photodynamic effect of a one-pot microwave produced C-DOTS based on citric acid. The in vitro assays assessed the effectiveness of illuminated C-DOTS (C-DOTS + Light) against Staphylococcus aureus suspension and biofilm. The concentrations of 6.9 and 13.8 mg/mL of C-DOTS and light doses of 20 and 40 J/cm2 were able to reduce significantly the microorganisms. Based on these parameters and results, the in vivo experiments were conducted in mice, evaluating this treatment on wounds contaminated with S. aureus. The viability test showed that C-DOTS-mediated photodynamic inactivation reduced 104 log of the bacteria present on the skin lesions. These results, altogether, showed that Antibacterial Photodynamic Therapy (aPDT) using C-DOTS is a promising and viable treatment for Gram-positive bacteria-infected wounds.